2018
DOI: 10.1007/s11367-018-1565-2
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of incorporating animal welfare in a social life cycle assessment model of European chicken production

Abstract: Purpose There is increasing public concern over standards of farm animal welfare, yet the majority of sustainability studies of livestock have thus far focused only on environmental performance and profitability. Where social analysis has been carried out, there has yet to be a consistent methodology developed that incorporates animal welfare into social life cycle assessment (S-LCA). A framework was developed to assess animal welfare, using conventional broiler chicken meat production in Europe as a case in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 71 publications
0
34
0
1
Order By: Relevance
“…Skin lesions 4 0 (no lesions, or <3 pecks or scratches); 1 (≥ one lesion <2 cm or ≥3 pecks or scratches); 2 (≥ one lesion ≥2 cm) 0 (normal, dextrous and agile); 1 (slight abnormality, but difficult to define); 2 (definite and identifiable abnormality); 3 (obvious abnormality, affects ability to move); 4 (severe abnormality, only takes a few steps); 5 (incapable of walking) 1 Welfare Quality ® assessment protocol for poultry, applied to broiler chickens. 2 Both feet/legs examined: bird scored according to most severe lesion observed. 3 Adapted from [22].…”
Section: Measure Scoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin lesions 4 0 (no lesions, or <3 pecks or scratches); 1 (≥ one lesion <2 cm or ≥3 pecks or scratches); 2 (≥ one lesion ≥2 cm) 0 (normal, dextrous and agile); 1 (slight abnormality, but difficult to define); 2 (definite and identifiable abnormality); 3 (obvious abnormality, affects ability to move); 4 (severe abnormality, only takes a few steps); 5 (incapable of walking) 1 Welfare Quality ® assessment protocol for poultry, applied to broiler chickens. 2 Both feet/legs examined: bird scored according to most severe lesion observed. 3 Adapted from [22].…”
Section: Measure Scoringmentioning
confidence: 99%
“…Observed flock mortality (post-slaughter) calculated with reference to original number of eggs/chicks and number of birds delivered to the abattoir. 2 Information obtained from computer production records. 3 Mortality rates including eggs not hatched/discarded due to lack of information on number of chicks hatched.…”
Section: Productionmentioning
confidence: 99%
“…There is thus far no generally applied approach to select the indicators that are used to assess animal welfare as part of sustainability. E.g., for broiler chickens on-farm behavioural observations and physiological indicators of stress have been used [15], but also a more extended set of indicators based on the 'five freedoms' [14], whereas others used a limited list based on published data [12] or routinely collected data in different countries [13], or even an overall welfare estimation per farming system [124]. For comparison of sustainability between laying hen farming systems, Van Asselt et al [11] selected data based on the four principles of the Welfare Quality ® poultry protocol [17], although they were only able to use a very limited set of indicators in their calculations for the animal welfare dimension.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the selection of indicators to be included in the welfare assessment model, we first defined a longlist of indicators. Earlier studies on sustainability of chicken farming included a very limited range of welfare indicators, usually based on data availability from literature or routinely collected farming chain data [11][12][13][14][15], but this may not fully represent the welfare issues in the farming chain and thus may not provide a complete picture of the actual welfare status. In our selection process, we aimed to cover all welfare aspects using the Welfare Quality ® approach [2] (see section 1.2) as a framework, using existing welfare assessment protocols where available.…”
Section: Approach To Develop a List Of Key-indicatorsmentioning
confidence: 99%
“…As an alternative to using a direct on-farm assessment like that of Welfare Quality ® to make cross-country assessments and comparisons of animal welfare outcomes, which, as argued above, is not practically feasible, it has been suggested (e.g., [28,29]) that meat inspection data is used to cover key aspects of animal welfare outcomes. However, previous studies have shown that different sources of meat inspection data may have serious differences in the threshold for recording.…”
Section: Limitations Of the Benchmark Approachmentioning
confidence: 99%